Overexpression of a flower‐specific aerolysin‐like protein from the dioecious plant Rumex acetosa alters flower development and induces male sterility in transgenic tobacco. (24th November 2016) - Manzano, Susana; Megías, Zoraida; Martínez, Cecilia; García, Alicia; Aguado, Encarnación; Chileh, Tarik; López‐Alonso, Diego; García‐Maroto, Federico; Kejnovský, Eduard; Široký, Jiří; Kubát, Zdeněk; Králová, Tereza; et al.
Summary: Sex determination in Rumex acetosa, a dioecious plant with a complex XY1 Y2 sex chromosome system (females are XX and males are XY1 Y2 ), is not controlled by an active Y chromosome but depends on the ratio between the number of X chromosomes and autosomes. To gain insight into the molecular mechanisms of sex determination, we generated a subtracted cDNA library enriched in genes specifically or predominantly expressed in female floral buds in early stages of development, when sex determination mechanisms come into play. In the present paper, we report the molecular and functional characterization of FEM32, a gene encoding a protein that shares a common architecture with proteins in different plants, animals, bacteria and fungi of the aerolysin superfamily; many of these function as β pore‐forming toxins. The expression analysis, assessed by northern blot, RT‐PCR and in situ hybridization, demonstrates that this gene is specifically expressed in flowers in both early and late stages of development, although its transcripts accumulate much more in female flowers than in male flowers. The ectopic expression of FEM32 under both the constitutive promoter 35S and the flower‐specific promoter AP3 in transgenic tobacco showed no obvious alteration in vegetative development but was able to alter floral organ growth and pollen fertility. The 35S::FEM32 and AP3::FEM32 transgenic lines showed a reduction in stamen development and pollen viability, as well as a diminution in fruit set, fruit development and seed production. Compared with other floral organs, pistil development was, however, enhanced in plants overexpressing FEM32 . According to these effects, it is likely that FEM32 functions in Rumex by arresting stamen and pollen development during female flower development. The aerolysin‐like pore‐forming proteins of eukaryotes are mainly involved in defence mechanisms against bacteria, fungi and insects and are also involved in apoptosis and programmed cell death (PCD), a mechanism that could explain the role of FEM32 in Rumex sex determination. Significance Statement: In Rumex acetosa, FEM32 gene encodes for a protein, whose structure and domains resembles those of the bacterial pore‐forming toxins of the aerolysin superfamily. The detailed characterization of the FEM32 molecular structure, and its overexpression in tobacco have suggested that it is probably involved in the arrest of stamen development and in pollen sterility.